Evaluating the Effective Management of the Deans of the Faculties of Physical Education and Sports Science According to the European Model (EFQM) (International Journal of Psychosocial Rehabilitation, 2020)
The researchers discussed the evaluation of the administrative methods used by the deans and the role of effective management of the deans of colleges of physical education and sports science according to the European model (EFQM) in order to find the most important reasons that help in developing the work of academic leaders to reach better results at the level of the global classification of education and the aim of the research was Identify the reality of effective management according to the European Excellence Model (EFQM) from the viewpoint of department heads and associates in colleges of physical education and sports science in Iraq. Where researchers used a tool based on the Iraqi environment to measure and evaluate the effective management of academic leaders from the point of view of Assam heads and assistants. The researchers used the descriptive method in the analytical survey method. The research sample reached from members of the teaching staff in colleges of physical education and sports sciences (Baghdad, Baghdad for girls, Al-Mustansiriya). As the number of colleges in Iraq reached 16, the total research community was 36 assistants and 42 department heads, and the research community as a whole was taken in an intentional manner (78). The current study recommended adopting effective management according to the European model in all government institutions. And building a strategy based on the foundations of effective management that meets the needs of the stakeholders. And work to diversify the information provided and dependent on the sources of information upon which the foundations of effective management are built. And work to update the principles of effective management in a very transparent and objective manner.